ENHANCING READING COMPETENCE THROUGH SHADOW READING: A COMPREHENSIVE APPROACH - Pulatova, Dilshifo Bahodirovna (Educational Research in Universal Sciences, 2023)
Reading competence is crucial for language acquisition and academic success. This study examines the efficacy of shadow reading in enhancing reading skills among language learners. Shadow reading, involving simultaneous reading with a proficient speaker, aims to improve pronunciation, fluency, and comprehension. The controlled study comprised 26 participants in the shadow-reading group and 21 in the non-shadow-reading group. Significant improvements were observed in the shadow-reading group’s fluency (25% increase), comprehension (30% improvement), and pronunciation accuracy (15% enhancement). These results underscore the effectiveness of shadow reading in augmenting reading abilities. Implications for educators, learners, and curriculum development are discussed, emphasizing the potential of integrating shadow reading into language learning programs.